Long-term oral bisphosphonate use in relation to fracture risk in postmenopausal women with breast cancer: findings from the Women's Health Initiative. Issue 11 (November 2016) - Drieling, Rebecca L.; LaCroix, Andrea Z.; Beresford, Shirley A.A.; Boudreau, Denise M.; Kooperberg, Charles; Chlebowski, Rowan T.; Gass, Margery; Crandall, Carolyn J.; Womack, Catherine R.; Heckbert, Susan R.
Abstract: Objective: The aim of the study was to examine the association of long-term oral bisphosphonate use, compared with short-term use, with fracture risk among postmenopausal women with breast cancer. Methods: We studied 887 postmenopausal women who were enrolled to the Women's Health Initiative from 1993 to 1998, diagnosed with breast cancer after enrollment, and reported current oral bisphosphonate use of 2 years or more on a medication inventory administered in 2008 to 2009. The outcome of any clinical fracture was ascertained by self-report on an annual study form; a subset of fractures was confirmed with medical records. Women were followed from completion of the medication inventory until 2014. The association between duration of bisphosphonate use reported on the medication inventory and fracture was estimated using multivariate Cox proportional hazards survival models that compared 4 to 7 years and 8 or more years of bisphosphonate use with 2 to 3 years of use. Results: On average, women were 76 years of age and were followed for 3.7 (SD 1.1) years. There were 142 clinical fractures. In the multivariate-adjusted analysis for fracture risk factors, 8 or more years of bisphosphonate use was associated with higher risk of fracture compared with 2 to 3 years of use (hazard ratio, 1.67 [95% CI, 1.06-2.62]). There was no significant association of 4 to 7 years of use with fracture. Conclusions: Bisphosphonate use of 8 or more years was associated with higher risk of any clinical fracture compared with 2 to 3 years of use. Our findings raise concern about potential harm or decreased effectiveness of long-term bisphosphonate use on fracture risk. The findings warrant confirmatory studies. Abstract : Supplemental Digital Content is available in the text